Organogenesis versus somatic embryogenesis pathway efficiencies in in vitro propagation of white and water yams - Ossai, C.; Balogun, M.; Maroya, N. (Springer, 2025)
The primary goal of this study was to compare the multiplication rates of yam varieties propagated through organogenesis and somatic embryogenesis (SE). Callus was induced from axillary bud explants of three genotypes of Dioscorea rotundata (Asiedu, Ekiti2a, and Kpamyo) and two genotypes of Dioscorea alata (Swaswa and TDa2014) cultured in Murashige and Skoog (MS) medium containing 9.1 µM 2,4-dichlorophenoxylacetic acid and 5.4 µM naphthaleneacetic acid. Plantlets were regenerated in MS containing 4.4 µM benzylaminopurine and 34 µM uniconazole-P through SE. Single-node cuttings of the five genotypes were grown in MS for 8 wk via organogenesis. The SE and organogenesis regenerants were acclimatized and potted in a 2 (propagation techniques (PTs)) × 5 (genotypes) factorial arranged in a completely randomized design (r = 10). The multiplication ratios (MR), number of tubers (NoT) of the SE, and organogenesis regenerants were collected and analyzed using ANOVA, and means were separated using DMRT (P ≤ 0.05). The SE and organogenesis MR ranged from 1:2 (TDa2014) to 1:8 (Asiedu) and 1:4 (Asiedu) to 1:5 (Ekiti2a and TDa2014), respectively. The NoT differed among genotypes, ranging from 1.15 ± 0.49 (Swaswa) to 2.45 ± 1.39 (Asiedu), and between PTs, ranging from 1.42 ± 0.70 (SE) to 1.86 ± 1.11 (organogenesis). The optimum propagation pathway was genotype-specific.